193k views
1 vote
What is "-2/3x" + 6 = 5

User Osantana
by
4.8k points

2 Answers

6 votes

Answer:


x = (2)/(3)

Explanation:

1. Remove the parentheses surrounding -2/3x

2. Move 6 to the other side. You'll get:


- (2)/(3x) = - 1

3. Multiply both sides of the equation by -3x (same as moving 1/3x to the other side). You'll get:


2 = 3x

4. Swapping the sides of the equation will make solving it easier:


3x = 2

5. Divide both sides of by 3 (same as moving three to the other side). You'll get:


* = (2)/(3)

User Kkopczak
by
5.5k points
4 votes

hope this helps

- 3/2

User Niranj Rajasekaran
by
4.8k points